Race Determinants of Wage Gaps in Colombia - Rojas-Hayes, Carolina M. (2012)
This paper examines the presence of wage gaps by race in Colombia. Information contained in the country's 2003 Living Standard Survey indicates that Afro-Colombian minorities--specifically, working age males--earn on average 6.4% less hourly wages than their non-Afro counterparts. In order to explain these differences, standard Mincerian equations are estimated. No statistical evidence of race discrimination in wages is obtained when controls for education levels, age, experience, geographical location, informality, and family size are included in the model. The most important statistically significant determinant of wages obtained was education levels. The results however do not rule out the existence of discriminatory practices in earlier stages in life that determine the quantity and quality of education as well as participation in the labor market. This result is corroborated by estimation of poverty and race. In this context, public policies that reduced differences in human capital endowments amongst Colombians of different ethnicities will contribute to decrease racial wage gaps.